Applying the Systems of Innovation approach to neighbourhood planning : assessing local development analysis through an appreciative study of two South African townships - Karuri-Sebina, JoAnne Wangechi (My University, 2015)
This thesis presents an appreciative application of the Systems of Innovation (SoI) approach to local development analysis (LDA) practice as applied in the context of a transformative approach to neighbourhood planning. The study’s point of departure is in interrogating what “lenses” conventional planning applies in making sense of neighbourhood-level realities in the first place, and therefore to recognise what it is that planning might “see” or fail to see in its analyses and prescripts. The researcher proposed to test this by undertaking an appreciative application of the Systems of Innovation (SoI) approach to neighbourhood planning to explore whether SoI contributes any additional perspective or insight beyond what conventional practice may have seen or found. The research undertaken was exploratory and inductive, involving data collection through intensive local observation and interviewing in two South African township neighbourhoods: T-Section in Mamelodi Township, and Saulsville node in Atteridgeville Township. The data was then analysed using an SoI model. The study found that the application of the SoI model identified additional key development considerations which were not previously recognised by conventional plans. Specifically, the findings highlight key social, economic and institutional factors which distinguish the two neighbourhoods from each other, and suggest different development intervention opportunities. The study also in addition identified an enhancement to the SoI model by introducing a spatial dimension which would strengthen the model’s application for planning and neighbourhood analysis. At the same time, however, the study also demonstrated the difficulty of applying the SoI framework to relatively deprived neighbourhood contexts, such as those in South African townships (or of describing these places as “systems of innovation” in the conventional sense) due to characteristic gaps and weaknesses, particularly their low technology base. The results of this study suggest that there are possible gaps in how conventional planning practices see local development contexts. It concludes that consideration should be given to what planning could glean from other disciplines which are grappling with similar transformational challenges, and adopting a transdisciplinary approach is motivated. Further research to support this continued exploration would have to address the main limitations of this study, which include the lack of generalizability, and limited interrogation of the limitations of SoI itself. Keywords: Local development analysis, System of Innovation, planning and transformation, neighbourhood development, township economy, transdisciplinarity
Keywords: City planning--South Africa; Innovative technology--Economic aspects; Technological innovations--South Africa